1999
DOI: 10.1016/s1097-2765(00)80219-1
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 Forms Complexes with the Cadherin/Catenin Cell–Cell Adhesion System and Is Recruited to Intercellular and Synaptic Contacts

Abstract: In MDCK cells, presenilin-1 (PS1) accumulates at intercellular contacts where it colocalizes with components of the cadherin-based adherens junctions. PS1 fragments form complexes with E-cadherin, beta-catenin, and alpha-catenin, all components of adherens junctions. In confluent MDCK cells, PS1 forms complexes with cell surface E-cadherin; disruption of Ca(2+)-dependent cell-cell contacts reduces surface PS1 and the levels of PS1-E-cadherin complexes. PS1 overexpression in human kidney cells enhances cell-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
188
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 49 publications
12
188
1
1
Order By: Relevance
“…Intriguingly, cellular phenotypes in PIP 2 -compromised cells are reminiscent of those observed in cells expressing FADassociated presenilin mutations, e.g., ion channel and trafficking deficits (15). The potential role of presenilin in PIP 2 metabolism can be further evidenced by occurrence of PS1 in PIP 2 -enriched subcellular compartments, including lipid rafts (44), phagocytic cups (19), lamellipodia (45), and adherent junctions (18). Thus, our study raises the possibility that PIP 2 may play a key role in the multiple cellular defects associated with presenilin FAD mutations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intriguingly, cellular phenotypes in PIP 2 -compromised cells are reminiscent of those observed in cells expressing FADassociated presenilin mutations, e.g., ion channel and trafficking deficits (15). The potential role of presenilin in PIP 2 metabolism can be further evidenced by occurrence of PS1 in PIP 2 -enriched subcellular compartments, including lipid rafts (44), phagocytic cups (19), lamellipodia (45), and adherent junctions (18). Thus, our study raises the possibility that PIP 2 may play a key role in the multiple cellular defects associated with presenilin FAD mutations.…”
Section: Discussionmentioning
confidence: 96%
“…Increasing evidence indicates that the presenilins are involved in several additional, ␥-secretase-independent cellular functions including Wnt and Akt signaling (12)(13)(14), membrane protein trafficking (15), ion channel regulation (16,17), and cell junction organization (18). Two of the most consistent cellular changes associated with both PS1 and PS2 FAD-associated mutations include ion channel dysfunction, such as defects in capacitative Ca 2ϩ entry (CCE) (16,17) and membrane trafficking defects, including diminished cell surface delivery of APP (15,(19)(20)(21).…”
mentioning
confidence: 99%
“…g-Secretase is thought to be an internal protease that cleaves within the membrane-spanning domain of all its substrate proteins. g-Secretase (PS1/NTF) is localized at the plasma membrane in cells with extensive cell-cell contacts (36)(37)(38)(39)(40)(41). On the basis of this g-secretase distribution, it did not seem that g-secretase would naturally favor Notch over E-cadherin cleavage in the well-formed spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…57 Besides these mechanisms, recent studies indicated that presenilins also mediate cleavage of synaptic-associated adhesion molecules such as nectin1␣ 58 and cadherins. 59 However, it remains to be determined whether PS1 cadherin/catenin interaction or PS-mediated cleavage of adhesion molecules play a functional role in synapse formation or modulate synaptic activity. 60 Thus, one can only speculate whether altered PS1-mediated cleavage of synaptic-associated adhesion proteins influenced synaptic function and integrity and was involved in the reported age-related loss of SIPBs within SR of the PS1 M146L mice.…”
Section: Alterations In Sipb Densities and Sipb Numbers In Ps1 M146l mentioning
confidence: 99%